Thermophysical properties of nanofluids MWCNT (multi-walled carbon nanotubes) in water for emergency coolant from nuclear reactors - Alexandre Melo Oliveira; Amir Zacarias Mesquita; Enio Pedone Bandarra; Daniel Flórez Morales (Brazilian Journal of Radiation Sciences)
To evaluate the synthesis and characterization of MWCNT (Multi-walled Carbon Nanotubes) with different degrees of functionalization in distilled water. The thermophysical properties (thermal conductivity and viscosity) of these nanofluids were measured at a temperature range (20-60°C) and concentrations (0.005-0.05%) by volume. Increases in thermal conductivity and viscosity were found 9.3% and 4.7%, respectively, at a volumetric concentration of 0.01% at a temperature of 30°C. The study of new fluids that improve the rate of removal of heat is fundamental to obtain greater efficiency of energy systems. Among the several factors that compromise the efficiency of the energy systems, we can highlight the thermophysical limitations of the conventional fluids, inhibiting in a very significant way some industrial applications. In this work we intend to improve the heat transfer characteristics of fluids commonly used by the addition of nanoparticles, made up of carbon nanotubes, in water which is the most used fluid for the cooling of nuclear reactors in operation today. It is intended to improve the heat transfer characteristics of fluids commonly used by the addition of nanoparticles, made of carbon nanotubes, through the addition of nanoparticles, made up of carbon nanotubes, in water which is the most used fluid for refrigeration of nuclear reactors currently in operation. In order to assess its benefits for the applicability and nuclear systems, ie primary coolant, safety systems, major accident mitigation strategies.